Makhá¹Å«á¹ah Anis al-MuttaqÄ«n li al-Shaikh al-Malik al-Fard Ê¿Abdu al-á¹¢amad bin FaqÄ«h á¸¤ussain bin FaqÄ«h Muá¸¥ammad - Zakiah, Nita (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2022)
This research examines a manuscript written by Shaikh Al-Malik Al-Fard Ê½Abdu Al-á¹¢amad Ibn FaqÄ«h á¸¤ussein Ibn FaqÄ«h Muá¸¥ammad. The study was divided into a description of the manuscript, transcribing the copy into the Malay language, and realizing the text and the essential ideas contained in the text. The objectives achieved are to present a representative edit of the text, to reveal the moral teachings in the text, and to explain the possibility of moral values that are relevant to present and future life. The research methodology used was philological research, data collection tools by conducting observations and recording. The steps of philological research include: determining research targets, inventorying manuscripts, statements, and manuscript descriptions, transliterating manuscripts, editing and translating texts, as well as summaries of the contents of the manuscripts and content analysis.ØªØ¨ØØ« Ù‡Ø°Ù‡ Ø§Ù„Ø¯Ø±Ø§Ø³Ø© ÙÙŠ Ø§Ù„Ù…Ø®Ø·ÙˆØ·Ø© Ø§Ù„ØªÙŠ ÙƒØªØ¨Ù‡Ø§ Ø§Ù„Ø´ÙŠØ® Ø§Ù„Ù…Ù„Ùƒ Ø§Ù„ÙØ±Ø¯ Ø¹Ø¨Ø¯ Ø§Ù„ØµÙ…Ø¯ Ø¨Ù† ÙÙ‚ÙŠÙ‡ ØØ³ÙŠÙ† Ø¨Ù† ÙÙ‚ÙŠÙ‡ Ù…ØÙ…Ø¯. ØªÙ… ØªÙ‚Ø³ÙŠÙ… Ø§Ù„Ø¨ØØ« Ø¥Ù„Ù‰ ÙˆØµÙ Ø§Ù„Ù…Ø®Ø·ÙˆØ·Ø©ØŒ ÙˆÙ†Ø³Ø® Ø§Ù„Ù†Ø³Ø®Ø© Ø¥Ù„Ù‰ Ø§Ù„Ù„ØºØ© Ø§Ù„Ù…Ù„Ø§ÙŠÙˆÙŠØ©ØŒ ÙˆØ¥Ø¯Ø±Ø§Ùƒ Ø§Ù„Ù†Øµ ÙˆØ§Ù„Ø£ÙÙƒØ§Ø± Ø§Ù„Ù…Ù‡Ù…Ø© Ø§Ù„ÙˆØ§Ø±Ø¯Ø© ÙÙŠ Ø§Ù„Ù†Øµ. Ø§Ù„Ø£Ù‡Ø¯Ø§Ù Ø§Ù„ØªÙŠ ØªÙ… ØªØÙ‚ÙŠÙ‚Ù‡Ø§ Ù‡ÙŠ ØªÙ‚Ø¯ÙŠÙ… ÙˆØªØ¹Ø¯ÙŠÙ„ ØªÙ…Ø«ÙŠÙ„ÙŠ Ù„Ù„Ù†ØµØŒ Ù„Ù„ÙƒØ´Ù Ø¹Ù† Ø§Ù„ØªØ¹Ø§Ù„ÙŠÙ… Ø§Ù„Ø£Ø®Ù„Ø§Ù‚ÙŠØ© ÙÙŠ Ø§Ù„Ù†ØµØŒ ÙˆØ´Ø±Ø Ø¥Ù…ÙƒØ§Ù†ÙŠØ© Ø§Ù„Ù‚ÙŠÙ… Ø§Ù„Ø£Ø®Ù„Ø§Ù‚ÙŠØ© Ø°Ø§Øª Ø§Ù„ØµÙ„Ø© Ø¨Ø§Ù„ØÙŠØ§Ø© Ø§Ù„ØØ§Ù„ÙŠØ© ÙˆØ§Ù„Ù…Ø³ØªÙ‚Ø¨Ù„ÙŠØ©. ÙˆÙ…Ù†Ù‡Ø¬ÙŠØ© Ø§Ù„Ø¨ØØ« Ø§Ù„Ù…ØªØ¨Ø¹Ø©ØŒ ÙˆØ§Ù„Ø¨ØÙˆØ« Ø§Ù„Ù„ØºÙˆÙŠØ©ØŒ ÙˆØ£Ø¯ÙˆØ§Øª Ø¬Ù…Ø¹ Ø§Ù„Ø¨ÙŠØ§Ù†Ø§Øª ØªÙ…Øª Ø¨Ø¥Ø¬Ø±Ø§Ø¡ Ø§Ù„Ù…Ù„Ø§ØØ¸Ø§Øª ÙˆØ§Ù„ØªØ³Ø¬ÙŠÙ„. ØªØ´Ù…Ù„ Ø®Ø·ÙˆØ§Øª Ø§Ù„Ø¨ØØ« Ø§Ù„Ù„ØºÙˆÙŠ: ØªØØ¯ÙŠØ¯ Ø£Ù‡Ø¯Ø§Ù Ø§Ù„Ø¨ØØ«ØŒ ÙˆØ¬Ø±Ø¯ Ø§Ù„Ù…Ø®Ø·ÙˆØ·Ø§ØªØŒ ÙˆØ§Ù„Ù…Ù„Ø§ØØ¸Ø§ØªØŒ ÙˆØ£ÙˆØµØ§Ù Ø§Ù„Ù…Ø®Ø·ÙˆØ·Ø§ØªØŒ ÙˆØªØ±Ø¬Ù…Ø© Ø§Ù„Ù…Ø®Ø·ÙˆØ·Ø§ØªØŒ ÙˆØªØØ±ÙŠØ± Ø§Ù„Ù†ØµÙˆØµ ÙˆØªØ±Ø¬Ù…ØªÙ‡Ø§ØŒ Ø¨Ø§Ù„Ø¥Ø¶Ø§ÙØ© Ø¥Ù„Ù‰ Ù…Ù„Ø®ØµØ§Øª Ù…ØØªÙˆÙŠØ§Øª Ø§Ù„Ù…Ø®Ø·ÙˆØ·Ø§Øª ÙˆØªØÙ„ÙŠÙ„ Ù…ØØªÙˆØ§Ù‡Ø§.